The origin of manganese formations at Cagalali Hill and Kevri.kevr Hill related to the late Triassic rifting of the South Neotethys, SE Turkey: The geological, mineralogical and geochemical components - Karatas, Burcu; Akyildiz, Mustafa; Yildirim, Nail; Yildirim, Esra (Pergamon-Elsevier Science Ltd, 2022)
The Kocali Complex includes continental rifting and subduction-related units that make up the southern Neotethys. This complex is a folded, tectonic-segmented succession with lavas, volcaniclastic sediments, pelagic carbonates, radiolarites and manganese deposits (the Tarasa and Konak formations) and ophiolitic units (the Kale formation). Manganese mineralizations in the host formation are found in banded, lenticular and massive forms within red to brown radiolarian cherts. Pyrolusite and polianite are the main manganese minerals, while psilomelane, manganite and minor hausmannite are other manganese minerals. Gangue minerals include quartz and carbonate, with minor barite being observed. The geochemical proofs (MnO: 8.98-73.64%, SiO2: 3.26-86%) originating from the main oxides indicates a hydrothermal rooted source for the manganese mineralization. This is confirmed by anomalies and trace element patterns including very low Fe/Mn (<0.1), low Co/Zn ratios (mean 0.86), very low Sigma REE contents (mean 34.67), slightly negative Eu* value (mean 0.74) and low Ce* value (mean -0.23). Manganese-oxide mineralizations observed in the volcanic sedimentary succession of the Kocali Complex have been interpreted as hydrothermal deposits associated with volcanism during the post-rifting seafloor extension of the southern Neotethys during the Late Triassic period.
Keywords: Southern Neotethys; Manganese mineralization; Geochemistry; Hydrothermal